2022
DOI: 10.1136/bmjopen-2021-055948
|View full text |Cite
|
Sign up to set email alerts
|

‘We are not going anywhere’: a qualitative study of Kenyan healthcare worker perspectives on adolescent HIV care engagement during the COVID-19 pandemic

Abstract: IntroductionAdolescents living with HIV (ALHIV) may be vulnerable to widescale impacts of the COVID-19 pandemic and to health system responses which impact HIV care. We assessed healthcare worker (HCW) perspectives on impacts of the COVID-19 pandemic on adolescent HIV care delivery and engagement in western Kenya.MethodsWe performed in-depth qualitative interviews with HCW at 10 clinical sites in the Academic Model Providing Access to Healthcare in Kenya, from January to March, 2021. Semistructured interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Eleven studies in total reported providing HIV treatment and care during COVID-19 remotely through telehealth services such as telephone and videoconferencing. Five of the studies were from the United States of America (USA) [ 50 , 52 , 59 , 60 , 68 ] and one each from Zambia [ 63 ], Myanmar [ 62 ], Philippines [ 65 ], Indonesia [ 56 ], Tanzania [ 51 ], and Kenya [ 54 ]. These studies reported that providers completed the required paperwork, including conducting needs assessments electronically, either through e-mail or over the phone, to minimise in-person contact with their clients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven studies in total reported providing HIV treatment and care during COVID-19 remotely through telehealth services such as telephone and videoconferencing. Five of the studies were from the United States of America (USA) [ 50 , 52 , 59 , 60 , 68 ] and one each from Zambia [ 63 ], Myanmar [ 62 ], Philippines [ 65 ], Indonesia [ 56 ], Tanzania [ 51 ], and Kenya [ 54 ]. These studies reported that providers completed the required paperwork, including conducting needs assessments electronically, either through e-mail or over the phone, to minimise in-person contact with their clients.…”
Section: Resultsmentioning
confidence: 99%
“…Service providers utilised different delivery approaches to overcome barriers to clients accessing ART during the COVID-19 pandemic, ensuring people on ART stayed supplied with their medications. For example, HIV service providers delivered ART to community dispensaries, community health centres, community pharmacies, and other community-based organisations [ 54 , 57 , 61 , 65 , 66 ]. Several services utilised their existing network of community-based health workers to deliver ART [ 52 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This unprecedented shift has impacted local health care workers, health care administrators, and the health systems in which they work. Like in many other countries, health care workers in Kenya have experienced increased stressors, anxiety, insomnia, depression, and burnout [35][36][37]. Although occupational challenges are being increasingly well documented, far less is known about the potential new understandings health care workers and health care administrators are gaining as they make meaning of their work, the health care system, and the role of global health activities in relation to the COVID-19 pandemic in Kenya.…”
Section: Covid-19 Global Pandemicmentioning
confidence: 99%